Characterization of the complete mitochondrial genome of the predatory mite Stratiolaelaps scimitus (Acari: Laelapidae). Issue 1 (2nd January 2020) - Yan, Yi; Zhang, Na; Wu, Xinran; Liu, Kai; Liu, Chenglin; Xie, Lixia
Abstract: In this study, we recovered the complete mitochondrial genome of Stratiolaelaps scimitus through Illumina sequencing data. The circularized mitogenome is 16, 009 in length, which consists of 37 genes (13 protein-coding genes, 22 transfer RNA genes, and 2 ribosomal RNA genes). The overall base composition is 35.4% for A, 40.1% for T, 16.8% for G, 7.7% for C, demonstrating an extreme bias of high AT content (75.5%). The whole mitogenome of S. scimitus and other Acari mitogenomes (10 species, in total) were used for phylogenetic analysis, and the result showed that the relationship of S. scimitus was close to Varroa destructor in the same Superfamily Dermanyssoidea.